Learning alliances: an approach for building multistakeholder innovation systems - Shaw, Alison; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Context: The Learning Alliance looks for leverage points for social learning in value chain systems and analysis linking rural farmers with markets. It uses an approach for building multistakeholder innovation systems that develop collaborative teams and learning platforms with development NGOs and their partners in order to learn over time about ways to link small farmholders to markets. The Rural Agroenterprise Development Project (1995) in cassava had tremendous success, however efforts to deliver tools and methods more broadly through a manual did not have the extent originally hoped. Learning platforms were developed to ensure greater relevance and appropriateness of knowledge and to extend the mobility of different knowledge, tools and approaches.